2018
DOI: 10.5435/jaaos-d-15-00063
|View full text |Cite
|
Sign up to set email alerts
|

Management of Sacroiliac Joint Pain

Abstract: Sacroiliac joint (SIJ)-based pain can be difficult to diagnose definitively through physical examination and conventional radiography. A fluoroscopically guided injection into the SIJ can be both diagnostic and therapeutic. The initial phase of treatment involves nonsurgical modalities such as activity modification, use of a sacroiliac (SI) belt, NSAIDs, and physical therapy. Prolotherapy and radiofrequency ablation may offer a potential benefit as therapeutic modalities, although limited data support their us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…Previous estimates of up to 30% of chronic back pain being referable to the SI joint have been published by numerous authors. [3][4][5][6][7] Recognition of this pathology has been limited in the past by a lack of clear diagnostic criteria. With increasing focus on this clinical entity, there is starting to be more consensus on appropriate means of diagnosing SI joint dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous estimates of up to 30% of chronic back pain being referable to the SI joint have been published by numerous authors. [3][4][5][6][7] Recognition of this pathology has been limited in the past by a lack of clear diagnostic criteria. With increasing focus on this clinical entity, there is starting to be more consensus on appropriate means of diagnosing SI joint dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 While the traditional focus of healthcare providers has been on lumbosacral pathology, sacroiliac joint dysfunction is an underappreciated and underdiagnosed cause of low back pain. Previous studies [3][4][5][6][7][8] have suggested that 15-30% of chronic low back pain is due to pathology located in the sacroiliac joint. Historically, recognition of this pathology was difficult, limited by lack of standardized diagnostic criteria and disease-specific outcome measures.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale for SI joint fusion is to relieve pain created by the movement of a joint through the removal of movement by arthrodesis of the joint space [39]. Only few comparative studies of percutaneous SI joint fusion and denervation have been reported, and they had limited clinical evidence [4041].…”
Section: Interventional Pain Management Optionsmentioning
confidence: 99%
“…These factors particularly put stress on the SIJ, thereby contributing to SIJ pain 4 . Anti‐inflammatory drugs and physical therapy are commonly used for treatment of SIJ pain 5 . However, anti‐inflammatory drugs can enter the fetal circulation through the placenta and show toxic effects in various tissues and organs.…”
Section: Introductionmentioning
confidence: 99%